'Becoming' factory workers: understanding women's geographies of work through life stories in Tamil Nadu, India. Issue 6 (3rd June 2019) - Dutta, Madhumita
Abstract: Feminist scholarship has drawn attention to the multiple places of labour and the intersection of social relations that shape women's geographies of work. Acknowledging feminist research on gender dynamics of globalization of production and household relations in 'making available' women's labour to the global capital, this article foregrounds explanations offered by the women, through their life stories, of their decisions to enter social relations of waged work. These young women worked in an electronics special economic zone in the southern Indian state of Tamil Nadu, where I argue that for women 'becoming' workers is not merely about entering into waged work or a scripted notion of class identity, but a complex process through which women's labour gets incorporated into the relations of (re)production and their ability to negotiate these relations to gain control over their bodies and labour. Their consciousness of 'becoming' workers is deeply embedded in their awareness and experiences of the gendered relations of labour at homes and their desire to change their life circumstances. Focusing on work-life experiences beyond employment relations, this article highlights the everyday 'micro-scale' struggles of women as they negotiate household relations of labour where escape and responsibility form part of their survival strategies and politics of work.